2022
DOI: 10.3390/ijerph19052836
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Determinants of First Nations Health Using a Four-Domain Model of Health and Wellness Based on the Medicine Wheel: Findings from a Community Survey in One First Nation

Abstract: We examined the explanatory roles of social determinants of health (SDOH) for First Nations people using a four-domain model of health and wellness based on the Medicine Wheel (i.e., physical, mental, emotional, and spiritual health), including colonial-linked stressors (i.e., historical trauma, childhood adversities, racial discrimination) and cultural resilience factors (i.e., cultural strengths, traditional healing practices, social support). Data were collected in partnership with a First Nation in Ontario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The results in the present study support the relationships described in the FNMWCF model-specifically, that belonging fostered through culture is a significant predictor of engagement in land-based activities. This finding supports existing models that describe how increased engagement in cultural practices and identities among Indigenous communities is protective against adverse physical and mental health outcomes, including racial discrimination, colonialism, and historical trauma [33,38,39,49]. For example, cultural resilience has been significantly associated with mental, physical, emotional, and spiritual wellbeing, including self-reported physical health [49].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results in the present study support the relationships described in the FNMWCF model-specifically, that belonging fostered through culture is a significant predictor of engagement in land-based activities. This finding supports existing models that describe how increased engagement in cultural practices and identities among Indigenous communities is protective against adverse physical and mental health outcomes, including racial discrimination, colonialism, and historical trauma [33,38,39,49]. For example, cultural resilience has been significantly associated with mental, physical, emotional, and spiritual wellbeing, including self-reported physical health [49].…”
Section: Discussionsupporting
confidence: 83%
“…It is possible that there may be a bidirectional relationship between individuals who use land-based activities to promote mental and physical health, not explored in the present study, as these strategies are used for both healing (i.e., those with lower mental health ratings) and general wellness promotion (i.e., likely those with higher mental health ratings). For example, a previous analysis of the use of traditional healing practices found that engagement in these practices was associated with poorer self-reported health [49]. The authors suggested that it was possible that individuals with diminished wellness may be more likely to seek such services to address these areas of need.…”
Section: Discussionmentioning
confidence: 99%
“…Physical wellness for Indigenous peoples is living a healthy, active lifestyle to maintain physical strength, fitness, and health (National Collaborating Centre for Aboriginal Health, 2013). Emotional wellness for Indigenous peoples can refer to affective or mood elements (Tanner et al, 2022).…”
Section: Four Dimensions Of Healthmentioning
confidence: 99%
“…To date, urban and off-reserve First Nations and Métis populations are dramatically underrepresented in health research (Koutouki & Lofts, 2019). Further, ways of evaluating mental health in the current Canadian health system differ from Traditional Indigenous Knowledges and ways of assessing wellness (Tanner et al, 2022). Operating from a colonial perspective and relying on Western approaches to healthcare when serving Indigenous communities and individuals further marginalizes and stigmatizes the unique challenges experienced by First Nations, Inuit, and Métis Peoples, and often is severely detrimental to their health.…”
Section: Introductionmentioning
confidence: 99%